Anagrelide treatment and cardiovascular monitoring in essential thrombocythemia. A prospective observational study. Issue 6 (June 2015) - Tortorella, Giovanni; Piccin, Andrea; Tieghi, Alessia; Marcheselli, Luigi; Steurer, Michael; Gastl, Günther; Codeluppi, Katia; Fama, Angelo; Santoro, Umberto; Birtolo, Chiara; Gugliotta, Gabriele; Cortelazzo, Sergio; et al.
Highlights: The in-depth CV evaluation before ANA was prospectively investigated in 55 ET pts. The in-depth CV evaluation was not necessary to define patients fit for ANA therapy. The in-depth CV evaluation before and during ANA did not predict CV adverse events. The CV adverse events during ANA were easily managed by the hematologists. The CV adverse events were cause of ANA withdrawal in only one of 38 patients (edema). Abstract: In this prospective observational single-center study, 55 patients with essential thrombocythemia who were candidates for second line treatment with anagrelide (ANA) received a preliminary cardiovascular (CV) clinical, instrumental and biochemical evaluation (CV history and symptoms, CV risk factors, blood pressure, heart rate, ECG and ECHO-cardio parameters, Troponin I, NT-proBNP). After this in-depth CV screening, 54 out of 55 patients were deemed to be fit for ANA treatment. Thirty-eight of the 55 patients received ANA treatment for a median of 36 months (range 3–48), and were monitored using the same CV evaluation. Fourteen of these 38 patients manifested CV adverse events (10 palpitation, 4 edema, 2 arterial hypertension, 2 acute myocardial infarction) that were not predicted by the in-depth CV evaluation, and that led to ANA withdrawal in only one case (non-cardiac refractory edema). In conclusion, the planned in-depth CV evaluation did not appear to be necessary in ET patients to evaluate their suitability for ANA treatment, and, moreover, was not able to predict the occurrence of CV adverse events during ANA treatment. Nevertheless, the CV adverse events (mostly palpitations and edema) were easily managed by the hematologists, and required the cardiologist involvement in very few selected cases.